ANALISA TEKNO EKONOMI PENGEMBANGAN USAHA BERBASIS KEARIFAN LOKAL KAB. SUMBA BARAT DAYA : BUBUR ROWE LUWA INSTAN - Nurhaidar Rahman; Nur Kartika Indah Mayasti; Ade Chandra Iwansyah; Ashri Indriati; Yusuf Andriana (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Rowe Luwa porridge is a local wisdom product from Southwest Sumba Regency (SBD), made from rice and the green colour of pounded sweet potato leaves. The instant Rowe Luwa porridge innovation enriched with sea fish meat and Moringa leaves is expected to provide added value to the product. Rowe Luwa instant porridge will extend shelf life and become a superior product of SBD. In starting a business development, technical and economic analysis is needed to determine whether the business is feasible or not to run. The selling price of 1 pack of 80 grams with a sales profit of 19.22% of Rp. 14,000, -. The results of the financial analysis of Rowe luwa instant porridge business obtained a Break-Even Point (BEP) unit per month of 588 packs, Net present value (NPV) of Rp. 110,173,149, Net B / C of 1.15, IRR of 44% and a payback period of 33 months. Based on the results of the calculation of financial analysis, it can be concluded that Instant Rowe luwa porridge's business is feasible to develop.